PX-478, an HIF-1α inhibitor, impairs mesoCAR T cell antitumor function in cervical cancer - Panahi Meymandi, Ahmad Reza; Akbari, Behnia; Soltantoyeh, Tahereh; Shahosseini, Zahra; Hosseini, Mina; Hadjati, Jamshid; Mirzaei, Hamid Reza (Frontiers in Oncology, 2024)
Chimeric Antigen Receptor (CAR) T cell therapy has demonstrated remarkable success in treating hematological malignancies. However, its efficacy against solid tumors, including cervical cancer, remains a challenge. Hypoxia, a common feature of the tumor microenvironment, profoundly impacts CAR T cell function, emphasizing the need to explore strategies targeting hypoxia-inducible factor-1α (HIF-1α). In this study, we evaluated the effects of the HIF-1α inhibitor PX-478 on mesoCAR T cell function through in-silico and in vitro experiments. We conducted comprehensive analyses of HIF-1α expression in cervical cancer patients and examined the impact of PX-478 on T cell proliferation, cytokine production, cytotoxicity, and exhaustion markers. Our in-silico analyses revealed high expression of HIF-1α in cervical cancer patients, correlating with poor prognosis. PX-478 effectively reduced HIF-1α levels in T and HeLa cells. While PX-478 exhibited dosedependent inhibition of antigen-nonspecific T and mesoCAR T cell proliferation, it had minimal impact on antigen-specific mesoCAR T cell proliferation. Notably, PX-478 significantly impaired the cytotoxic function of mesoCAR T cells and induced terminally exhausted T cells. Our results underscore the significant potential and physiological relevance of the HIF-1α pathway in determining the fate and function of both T and CAR T cells. However, we recognize the imperative for further molecular investigations aimed at unraveling the intricate downstream targets associated with HIF-1α and its influence on antitumor immunity, particularly within the context of hypoxic tumors. These insights serve as a foundation for the careful development of combination therapies tailored to counter immunosuppressive pathways within hypoxic environments and fine-tune CAR T cell performance in the intricate tumor microenvironment.